Pengujian Thermoelectric Generator (TEG) Dengan Sumber Kalor Electric Heater 60 Volt Menggunakan Air Pendingin Pada Temperatur Lingkungan - Nugrah Suryanto; Azridjal Aziz; Rahmat Iman Mainil (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Thermoelecric is a phenomena to convert from temperature difference into electrical energy that can be called Thermoelectric Generator (TEG) or from electrical energy into temperature difference that is called Thermoelectric Cooling (TEC). The Thermoelectric Generator (TEG) principle is known as the seebeck effect, while the Thermoelectric Cooling (TEC) principle is known as peltier effect. The purpose of this research to determine the effect of thermoelectric module number on maximum power, maximum voltage and maximum efficiency. This research uses thermoelectric module, type TEG SP 1848. The cold side of thermoelectric module uses water at ambient temperature with flow rate 1.7 liter / minute. With a input voltage regulator of 60 V to heat the electric heater. From the test using 1 module, 2 module, 3 module, and 4 module thermoelectric type TEG SP 1848, the maximum voltage of 0.39 V, 0.47 V, 0.54 V, and 0.62 V, the maximum power generated of 0.032 W, 0.082 W, 0.164 W, and 0.272 W and the maximum efficiency of 0.36%, 0 .42%, 0.92%, and 1.30%. The more number of thermoelectric modules used during the test, the resulting voltage, power and efficiency will increase.Keywords : thermoelectric generator, seebeck effect